Genetic Diversity and Relationships of Dendrobium Based on TrnL-F Markers: An Approach In-silico - Ismail, Ikhwan; Mahfut, Mahfut (Tropical Genetics, 2025)
The development of DNA sequencing technologies has deepened our understanding of genetic variation within Dendrobium species and revealed evolutionary relationships among them. in-silico methods facilitate efficient phylogenetic determination, leveraging computational advantages to process sequence data with high accuracy. This study aims to significantly contribute to the understanding of genetic diversity within the genus Dendrobium based on the TrnL-F marker, with potential implications for the conservation and management of these plant genetic resourcesThis paper presents nucleotide diversity analysis and phylogenetic analysis to determine the kinship relationships among Dendrobium species. The analysis revealed a high degree of relatedness among the Dendrobium species, with kinship relationships dividing them into three distinct groups.